Exploring pilgrims’ information behaviour and spiritual skills development - Wafa, Ebtihal; Innocenti, Perla; Ruthven, Ian (Information Research an international electronic journal, 2025)
Introduction. An understanding of pilgrim information behaviour in relation to spiritual skills development is barely represented in information science. This research explores the dynamics and interrelations between Hajj pilgrims’ information practices, information needs and spiritual skills development. Method. The initial phase of research investigates pilgrims’ information behaviour through an online semi-structured survey in Arabic and English. This overview of the demographics, information behaviour, learning processes and spiritual skills development before, during and after the Hajj provides an initial understanding of pilgrims’ information practices. Analysis. Completed survey responses from 126 participants were analysed using reflexive thematic analysis. Results. The Hajj constitutes a transformative experience in which information behaviours, learning strategies and spiritual practices intersect. Findings highlight the pivotal roles of trust, accessibility and community in supporting and influencing pilgrims’ experiences; the blending of traditional and digital resources; and the importance of a communal environment for learning and fostering spiritual development. Conclusions. This study contributes to understanding how Hajj pilgrims obtain and use information during this sacred journey, and their underlying information needs, preferred media and formats and learning strategies to cultivate and nurture spirituality.